Well-Designed Food Governance as Psychological Mechanism of Consumer Perceptions in the Context of Tourism Poverty Alleviation - Huang, Guo-qing; Lin, Kuen-Lin (Frontiers in Psychology, 2021)
Poverty is a challenge leading to food insecurity in people’s minds. This article discusses food governance as a psychological mechanism to facilitate the sense of wellness in people’s minds in the context of poverty alleviation. Mainly, we argued that when government is implementing poverty alleviation, not only economic efforts for people’s living, but also good psychological feelings are required. We thus argued that a sound food governance may increase the sense of wellness in the minds of people as food consumers, by increasing food safety and security. This perspective paper contributes by explicating the influences of macro-level governance design in safer and more secure food system on people’s psychological wellness, especially in the background of poverty alleviation in developing countries.